Distance of Apical Constriction to the Apical Foramen in Extracted Lower First Premolar Teeth Assisted by Per Apical Radio-graph in Kerbala City - Sameer Hatem Abdul Haleem (Journal of Global Pharma Technology, 2018)
The purpose of this study was to investigate the measurement of the site of apical constriction in the lower first premolar teeth of radio-graphically in Kerbala AL-Mukadissa samples of patients who's attending to the dental clinic for orthodontic treatment,62 lower premolar teeth were examined radio-graphically for the size of the apical constriction, all these teeth were sound and caries free, these teeth examined radio graphically for detection of the apical constriction and the radiographic apex by using size 20 K file inside the root canal  and the difference between the two were calculated as a measurement for the apical constriction size, the size of apical constriction was found 0.4-1.5mm, the man was found = 0.864 mm for the whole sample.Keywords:  Apical foramen, Apical constrictions, Per-apical radiograph.